Road To Be A Millionaire In Danny Boyle's Slumdog Millionaire Movie (2008): A Marxist Approach - Harris, Alfian; , Drs. Abdillah Nugroho, M.Hum; , Nur Hidayat S.Pd (2013)
This study describes the road to be a millionaire view in Danny Boyles's "Slumdog Millionaire" movie from marxist approach, and analyzes the movie based on its structural elements. The research is conducted by using qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is film Slumdog Millionaire directed by Danny Boyle. The secondary data source are the books about marxist and the other sources, which are related to the analysis. The method of collecting data is observation and library review. Based on the analysis, the study reveals that there are some aspects underlying the road to be Millionaire. Dialectical materialism deals with the struggle to change life from destitution in a road to be millionaire. Definition of historical materialism portrayed into oppressor and oppressed. Alienation process is expressed, when the vagrants feel alienated because they have not knowledge and live in poor condition. Class struggle focuses on the struggle of the oppressed class against the oppressor. Revolution in this movie story takes place after Jamal as an oppresed is being a Millionaire.